Long-term Effect of Intra-Row Spacing on Growth and Productivity of Super-High Density Hedgerow Olive Orchards (cv. Arbequina) - Gomez-del-Campo, Maria; Connor, David J.; Trentacoste, Eduardo R. (Frontiers in Plant Science, 2017)
Intra-row spacing is known to determine early productivity of super-high density olive orchards depending on growing conditions, cultivar growth characteristics, planting geometry and subsequent pruning management but few experiments have been carried out in this olive hedgerow orchard design. In 2008 an experiment of 4-m spaced hedgerows was established with 8 intra-row spacings (from 1.0 to 2.5 m) in Toledo (Spain) resulting in orchards of density ranging from 2500 to 1000 trees ha-1. Tree growth was evaluated as height, trunk diameter and leaf area during the first 4 years. Hedgerow porosity was calculated from the 4th until the 9th year. In the 8th year hedgerow height, width, leaf area and branch angles were measured. Olives were harvested from 3rd to 9th year for measurements of fruit characteristics and productivity. Tree growth was not affected by intra-row spacing during the first 4 years. In the 8th year leaf area, external surface area and volume per tree were significantly greater in the more spaced trees; but hedgerow characteristics of leaf area per hectare, number of effective leaf layers horizontally through the hedgerow, and leaf density were not affected. In the more spaced trees insertion angles of branches to the vertical were significantly greater, mainly in the lower canopy. Intra-row spacing did not affect fruit characteristics. Oil production ha-1 decreased linearly with spacing during the first 4 harvests while production per tree increased significantly with spacing after the 5th year. As a result, oil production ha-1 from the seven harvests combined only increased for tree spacing less than 1.2 m; wider spacing had no effect. Annual oil production ha-1 increased linearly as porosity was reduced by greater tree density and canopy development along the seasons.